GYNAECOMASTIA: MANAGEMENT IN A DEVELOPING COUNTRY - Muneer, Ambreen; Laghari, Zameer Hussain; Shaikh, Abdul Razaque; Laghari, Qamber Ali (Journal of Ayub Medical College Abbottabad, 2009)
Background: Gynaecomastia is a benign enlargement of male breast. It is common in the general population, resulting from various pathophysiological mechanisms. The aim of this study was to describe the presentation and outcome of treatment for gynaecomastia at a University Hospital in Pakistan. Methods: A three year retrospective study was carried out of one hundred men with gynaecomastia. Patients were evaluated in detail clinically and by appropriate investigations. They were counselled and kept on hormonal therapy for three months. Surgery was considered for patients with long standing gynaecomastia, failed medical therapy and for cosmetic reasons. Post operative complications and patient’s satisfaction was assessed. Results: Most (90%) cases were idiopathic. Other causes were liver cirrhosis in 4 cases, testicular tumour in two, thyrotoxicosis in one and drug induced (use of cimetidine and Kushta) in two. Carcinoma of the breast was diagnosed in one patient. Most of the patients had bilateral, non tender lump in the breast. Three cases of idiopathic gynaecomastia resolved on danazol. Eighty-eight cases underwent surgical treatment. The mean age of patients who underwent surgery (n=88) was 30.5±9.59 years. Most of the patients belonged to 21-30 years age group. Major indications for surgery were failure of medical treatment (45.5%) and cosmetic reasons (34.0%). Mean operating time for subcutaneous mastectomy was 42.2±3.70 (36-48) minutes. Mean hospital stay after subcutaneous mastectomy was 5.2±2.44 (2-10) days. The only postoperative complication noted was wound infection (24%). Seventy-two (81.8%) were satisfied with the results of their surgical treatment. Conclusion: Gynaecomastia is the common condition affecting male breasts and most common cause of gynaecomastia is idiopathic. Secondary gynaecomastia may regress in size by treating the primary cause. Idiopathic gynaecomastia do not respond to danazol so they needed surgical treatment. Subcutaneous mastectomy through a periareolar skin incision is a valid procedure for treatment for gynaecomastia and provides satisfactory cosmetic results. Keywords: Gynaecomastia, Male breast, Management, Subcutaneous mastectomy